Synthesis and Properties of Isobicyclo‐DNA. Issue 22 (23rd April 2013) - Gerber, Anna‐Barbara; Leumann, Christian J.
Abstract We present the synthesis of the isobicyclo‐DNA building blocks with the nucleobases A, C, G and T, as well as biophysical and biological properties of oligonucleotides derived thereof. The synthesis of the sugar part was achieved in 5 steps starting from a known intermediate of the tricyclo‐DNA synthesis. Dodecamers containing single isobicyclo‐thymidine incorporations, fully modified A‐ and T‐containing sequences, and fully modified oligonucleotides containing all four bases were synthesized and characterized. Isobicyclo‐DNA forms stable duplexes with natural nucleic acids with a pronounced preference for DNA over RNA as complements. The most stable duplexes, however, arise by self‐pairing. Isobicyclo‐DNA forms preferentially B‐DNA‐like duplexes with DNA and A‐like duplexes with complementary RNA as determined by circular dichroism (CD) spectroscopy. Self‐paired duplexes show a yet unknown structure, as judged from CD spectroscopy. Biochemical tests revealed that isobicyclo‐DNA is stable in fetal bovine serum and does not elicit RNaseH activity.